Substitution Of Dragon Fruit Skin As Herbal Tea To Prevent More Nutrition (Obesity) - Widya Sasmita; Eliska Eliska (Jurnal Ners, 2023)
The research discusses the substitution of specific nutrients into food products to resemble or replace other food products with higher nutritional value. The substituted food is commonly used as an alternative food product. In this study, I will create an herbal tea using dragon fruit peel, which can help prevent or address nutritional issues. Method: This research employed an experimental design using a Completely Randomized Design (CRD) with three different treatments: P1 (dragon fruit peel with drying temperature of 40°C), P2 (dragon fruit peel with drying temperature of 50°C), and P3 (dragon fruit peel with drying temperature of 60°C). Data collection was conducted through organoleptic/hedonic (preference) tests, evaluating the taste, texture, color, and physical appearance of the prepared dragon fruit peel tea, which was given to 25 untrained panelists. Conclusion: It can be concluded that the preferred color of the herbal tea made from dragon fruit peel was found in treatment P1, with a score of 4.16, using a drying temperature of 40°C for approximately 30 minutes. The preferred aroma of the dragon fruit peel herbal tea was also found in treatment P1, with a score of 4.24, using a drying temperature of 40°C for approximately 30 minutes. The preferred taste of the dragon fruit peel herbal tea was found in treatment P1, with a score of 4.44, using a drying temperature of 40°C for approximately 30 minutes. This indicates that a lower temperature resulted in less dry dragon fruit peel, leading to more appealing color, aroma, and taste.